Infrastructuring Gardens: The Material Politics of Outdoor Water Conservation in Los Angeles. (2nd January 2023) - Meilinger, Valentin; Monstadt, Jochen
Abstract : Historically, urban developers, politicians, and public water utilities have invented Los Angeles as a semitropical oasis in a dry climate. During the California drought of 2011 through 2016, however, the city's residential gardens became a new frontier of water conservation policy. Water agencies started to subsidize the replacement of lushly irrigated lawns with California Friendly® landscapes, thereby endorsing a technology-centered "infrastructuring" of gardens to increase water conservation. This approach contrasts with California native plant gardening promoted by nature conservationists, which uses vernacular horticultural techniques to restore native plant biodiversity and reduce irrigation. The article shows that each approach has important political implications for urban space and water use, the value accorded to nature and gardening work, and relations between citizens and experts. Analyzing the differences between these approaches, we critically interrogate Los Angeles's modern infrastructure regime that shapes water conservation policy. Particular attention is paid to how new material objects, knowledges, and practices in gardening recompose relationships between water, plants, technology, humans, and urban space. We argue that the notion of infrastructuring gardens offers a fruitful lens for ascertaining how expert cultures shape urban environmental change and how alternative gardening practices (re)produce urban nature differently.